2015
DOI: 10.1089/sur.2013.135
|View full text |Cite
|
Sign up to set email alerts
|

An Ounce of Prevention Saves Tons of Lives: Infection in Burns

Abstract: The treatment of infection and sepsis against highly adaptable bacteria is often insurmountable by ill patients. In this process, bioburden needs to be corralled to have any success. Thus, preventing organisms from entering the unit and transferring onto other patients, and eliminating the bacteria dwelling in the unit are all necessary actions in this battle. Ultimately, maintaining a culture that is constantly wary of this risk only can achieve this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 75 publications
(71 reference statements)
0
9
0
1
Order By: Relevance
“…A study using HSE models has shown that reduced expression of filaggrin protein resulted in increased epidermal S. aureus colonization . S. aureus is also a major pathogen in skin infections in burn wound patients, and large efforts are made to prevent and treat wound infections . The expectation is that many studies will investigate the role of micro‐organisms in skin diseases and therapeutic strategies to treat these conditions.…”
Section: The Skin Microbiome: a Novel Player In Skin Barrier Researchmentioning
confidence: 99%
“…A study using HSE models has shown that reduced expression of filaggrin protein resulted in increased epidermal S. aureus colonization . S. aureus is also a major pathogen in skin infections in burn wound patients, and large efforts are made to prevent and treat wound infections . The expectation is that many studies will investigate the role of micro‐organisms in skin diseases and therapeutic strategies to treat these conditions.…”
Section: The Skin Microbiome: a Novel Player In Skin Barrier Researchmentioning
confidence: 99%
“…Among that group, Staphylococcus aureus continues to be one of the most important bacterial cause of burn wound infections [4][5][6][7]. The most frequently isolated Gram-negative bacteria from patients with burn wounds include Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella spp., Stenotrophomonas spp., Escherichia coli, and Enterobacter cloacae [1,2,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is described as organ damage in the context of a dysregulated systemic inflammatory response to an infectious agent [69]. It is a primary cause of mortality in intensive care units worldwide and is presently the leading cause of death in patients with severe burns [70]. Due to this, sepsis has been the topic of much recent study and discussion.…”
Section: Sepsis In Burnsmentioning
confidence: 99%
“…As a result, rigorous infection prevention and control measures are the norm in modern burn units in an attempt to reduce the likelihood of infection. These measures include screening for resistant organisms upon admission and discharge of patients, individual patient rooms, contact isolation measures, a strong emphasis on hygiene, daily antimicrobial dressings for burn wounds, monitoring of need and status of all invasive catheters, and careful antimicrobial stewardship [70].…”
Section: Sepsis In Burnsmentioning
confidence: 99%